High-intensity downhill running exacerbates heart rate and muscular fatigue in trail runners. Issue 7 (3rd April 2021) - Lemire, Marcel; Remetter, Romain; Hureau, Thomas J.; Kouassi, Blah Y. L.; Lonsdorfer, Evelyne; Geny, Bernard; Isner-Horobeti, Marie-Eve; Favret, Fabrice; Dufour, Stéphane P.
ABSTRACT: This study explores the cardiorespiratory and muscular fatigue responses to downhill (DR) vs uphill running (UR) at similar running speed or similar oxygen uptake (⩒O2 ). Eight well-trained, male, trail runners completed a maximal level incremental test and three 15-min treadmill running trials at ±15% slope: i) DR at ~6 km·h −1 and ~19% ⩒O2max (LDR); ii) UR at ~6 km·h −1 and ~70% ⩒O2max (HUR); iii) DR at ~19 km·h −1 and ~70% ⩒O2max (HDR). Cardiorespiratory responses and spatiotemporal gait parameters were measured continuously. Maximal isometric torque was assessed before and after each trial for hip and knee extensors and plantar flexor muscles. At similar speed (~6 km·h −1 ), cardiorespiratory responses were attenuated in LDR vs HUR with altered running kinematics (all p < 0.05). At similar ⩒O2 (~3 l·min −1 ), heart rate, pulmonary ventilation and breathing frequency were exacerbated in HDR vs HUR ( p < 0.01), with reduced torque in knee (−15%) and hip (−11%) extensors and altered spatiotemporal gait parameters (all p < 0.01). Despite submaximal metabolic intensity (70% ⩒O2max ), heart rate and respiratory frequency reached maximal values in HDR. These results further our understanding of the particular cardiorespiratory and muscular fatigue responses to DR and provide the bases for future DR training programs for trail runners.